Efficacy and safety of different doses and retreatment of rituximab: a randomised, placebo-controlled trial in patients who are biological naïve with active rheumatoid arthritis and an inadequate response to methotrexate (Study Evaluating Rituximab's Efficacy in MTX iNadequate rEsponders (SERENE)). Issue 9 (20th May 2010) - Emery, P; Deodhar, A; Rigby, W F; Isaacs, J D; Combe, B; Racewicz, A J; Latinis, K; Abud-Mendoza, C; Szczepański, L J; Roschmann, R A; Chen, A; Armstrong, G K; et al.
Abstract : Objectives: This phase III study evaluated the efficacy and safety of rituximab plus methotrexate (MTX) in patients with active rheumatoid arthritis (RA) who had an inadequate response to MTX and who were naïve to prior biological treatment. Methods: Patients with active disease on stable MTX (10–25 mg/week) were randomised to rituximab 2×500 mg (n=168), rituximab 2×1000 mg (n=172), or placebo (n=172). From week 24, patients not in remission (Disease Activity Score (28 joints) ≥2.6) received a second course of rituximab; patients initially assigned to placebo switched to rituximab 2×500 mg. The primary end point was American College of Rheumatology 20 (ACR20) response at week 24. All patients were followed until week 48. Results: At week 24, both doses of rituximab showed statistically superior efficacy (p<0.0001) to placebo (ACR20: 54%, 51% and 23%; rituximab (2×500 mg) + MTX, rituximab (2×1000 mg) + MTX and placebo + MTX, respectively). Secondary end points were also significantly improved for both rituximab groups compared with placebo. Further improvements in both rituximab arms were observed from week 24 to week 48. Rituximab + MTX was well tolerated, demonstrating comparable safety to placebo + MTX through to week 24, and between rituximab doses through to week 48. Conclusions: Rituximab (at 2×500 mg and 2×1000 mg) plus MTX significantly improved clinical outcomes at week 24, which were further improved by week 48. No significant differences in either clinical or safety outcomes were apparent between the rituximab doses.